Tinjauan Hukum Terhadap Pernikahan Anak Perempuan Diluar Perkawinan Oleh Ayah Biologisnya Menurut Hukum Islam - Jaya, Febri; Fitri, Winda; Mahardhika, Delvin Shakira (UMPurwokerto Law Review, 2024)
Abstract In Islam, the marriage of a girl outside of a legitimate marriage by her biological father is related to the validity of the marriage status. This research aims to examine the Islamic law perspective regarding the validity of the marriage status of a girl outside of a legitimate marriage by her biological father and the legal protections afforded to them. The research will employ a normative legal method to analyze Islamic legal texts and relevant legislation. Data sources will include Islamic legal texts, legislation, scholarly opinions, and Islamic legal literature, using a descriptive and comparative analysis approach to data analysis. The research findings indicate that in Islamic law, the validity of the marriage of a girl outside of a legitimate marriage, officiated by her biological father as the guardian, is a complex and debated issue. Invalid marriages in Islamic law and the Marriage Law have legal and social consequences, particularly concerning the rights of the girls involved. Legal protection for girls born outside of marriage in Islamic law in Indonesia involves various aspects. In Islam, children are revered as trusts that must be cared for and provided with protection and affection, especially by their biological fathers. Fathers have obligations for financial support, education, protection, and affection towards their children, including those born outside of marriage, as well as moral responsibilities in teaching religious and ethical values. Keywords: Islamic law, position of children out of wedlock, rights of children out of wedlock. Â Abstrak Dalam Islam, pernikahan anak perempuan di luar perkawinan oleh ayah biologisnya berkaitan dengan keabsahan status perkawinan. Penelitian ini bertujuan untuk mengkaji pandangan hukum Islam terkait keabsahan status perkawinan anak perempuan di luar perkawinan oleh ayah biologisnya serta perlindungan hukum diberikan kepada mereka. Penelitian ini akan menggunakan metode hukum normatif untuk menganalisis teks-teks hukum Islam dan peraturan perundang-undangan terkait. Sumber data meliputi teks-teks hukum Islam, peraturan perundang-undangan, pendapat ulama, dan literatur hukum Islam, dengan pendekatan analisis deskriptif dan komparatif dalam analisis data. Hasil penelitian menunjukkan bahwa dalam hukum Islam, keabsahan perkawinan anak perempuan di luar perkawinan yang sah yang dinikahkan oleh ayah biologisnya sebagai wali nikah menjadi subjek perdebatan yang kompleks. Perkawinan yang tidak sah dalam hukum Islam dan UU Perkawinan memiliki konsekuensi hukum dan sosial terutama terkait dengan hak-hak anak perempuan. Perlindungan hukum terhadap anak perempuan yang dilahirkan di luar perkawinan dalam hukum Islam di Indonesia melibatkan berbagai aspek. Dalam Islam, anak-anak dihormati sebagai amanah yang harus dijaga dan diberikan perlindungan serta kasih sayang, terutama ayah biologis. Ayah memiliki kewajiban nafkah, pendidikan, perlindungan, dan kasih sayang terhadap anak-anak, termasuk yang lahir di luar perkawinan, serta tanggung jawab moral dalam pengajaran nilai-nilai agama dan etika. Kata kunci: hukum islam, kedudukan anak di luar nikah, hak anak di luar nikah.